5-Fluorouracil-induced acute reversible heart failure not explained by coronary spasms, myocarditis or takotsubo: lessons from MRI. (1st June 2016) - Fakhri, Yama; Dalsgaard, Morten; Nielsen, Dorte; Lav Madsen, Per
Abstract : A 69-year-old woman presented with arterial hypotension, pulmonary oedema and a severely depressed left ventricular ejection fraction (LVEF) of 25% only 3 days after having received her first treatment for colorectal cancer with 5-fluorouracil (5-FU)-based therapy. The ECG demonstrated widespread ST-segment depression and echocardiography showed uniform hypokinesia of all left ventricular (LV) myocardial segments without signs of regional LV ballooning. Coronary angiography was normal and the patient gained full recovery after receiving treatment with heart failure medication. Interestingly, cardiac MRI scan 9 days later showed a normal LVEF with signs of neither myocardial oedema nor necrosis. Despite the high therapeutic efficacy of 5-FU in treatment of colorectal cancer, it is associated with undesired cardiac toxicities including coronary spasms, toxic inflammation and takotsubo cardiomyopathy. However, our patient did not fulfil the diagnostic criteria for the aforementioned complications. Based on this case report, we discuss alternative mechanisms including myocardial adenosine triphosphate depletion suggested from animal experiments.